2002
DOI: 10.1583/1545-1550(2002)009<0810:copsbp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Periprocedural Systolic Blood Pressure Changes With Neurological Events in High-Risk Carotid Stent Patients

Abstract: Patients with severely elevated baseline SBP (>180 mmHg) may be at higher risk for hemodynamic instability and neurological events during carotid stenting. The greater the change in SBP, the more severe the neurological event seems to be, but further studies in a greater number of patients are needed to evaluate the potential causes of SBP fluctuations in an effort to avoid neurological events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 16 publications
2
31
1
Order By: Relevance
“…[17][18][19][20] However, this association has not been found in every study. [21][22][23] In the current study, 12% of the patients treated by CAS had periprocedural hemodynamic depression requiring treatment, whereas uncontrolled series of patients treated by CAS have reported frequencies of arterial hypotension or hemodynamic depression ranging from 19% to 51%.…”
Section: Discussionmentioning
confidence: 84%
“…[17][18][19][20] However, this association has not been found in every study. [21][22][23] In the current study, 12% of the patients treated by CAS had periprocedural hemodynamic depression requiring treatment, whereas uncontrolled series of patients treated by CAS have reported frequencies of arterial hypotension or hemodynamic depression ranging from 19% to 51%.…”
Section: Discussionmentioning
confidence: 84%
“…Caplan et al 8) suggested that emboli are not washed out due to a reduced perfusion pressure of the brain as a mechanism of cerebral infarction, and Howell et al 9) reported that the frequency of ischemic neurological symptoms increased significantly when the SBP decreased by 51 mmHg or more in the peri-CAS period compared with the usual pressure. We administered noradrenaline to all such patients to promptly increase the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hypotension lasting Ͼ1 hour was also assessed because this has previously been shown to relate to adverse neurological outcome, 6 although the magnitude of the change in systolic blood pressure (Ͼ50 mm Hg) has recently also been shown to relate to adverse neurological events after carotid stenting. 13 Comparison between the 2 groups in this regard was subject to bias because the surgical group received more active treatment. Furthermore, the surgical technique can influence the type of blood pressure disturbances seen, so that dissection methods that preserve the carotid nerve result in fewer episodes of hypertension.…”
Section: Mckevitt Et Al Effect Of Carotid Interventions On Blood Presmentioning
confidence: 99%